Natural durability of Eucalyptus species harvested as electricity transmission poles in two different ecological zones of Ghana - Francis Wilson Owusu; Mary Mamle Apetorgbor; James Kofi Korang; Courage Alorbu; Emmanuel Appiah-Kubi; Rado Gazo; Francis Asare (Scientific African, 2024)
This study assessed the possibility and feasibility of using two Eucalyptus species for electricity transmission poles in Ghana as a means of minimizing the import of transmission poles in the country. Eucalyptus species are grown in private and government-owned plantations in Ghana due to its growing demand for use as power line transmission poles. The species are seldom used by the furniture industry. The demand from the pole treatment industry for raw materials exceeds the domestic supply of teak, which is commonly used as transmission poles, resulting in the importation of pine poles to cover the deficit, hence the need for this study. The natural durability of Eucalyptus alba and Eucalyptus robusta in the Coastal Savanna Zone (CSZ) and Moist Semi-Deciduous Forest Zone (MSDFZ) was tested using white rot fungus (Coriolopsis polyzona) under an accelerated laboratory test. The results indicated significant variations in the mass lossess be-tween trees in the two vegetation zones. The sapwood and outer heartwood of the E. alba tree species of CSZ recorded the highest mass losses of 41.21 % and 20.79 %, respectively, compared to the E. robusta trees felled from MSDFZ that recorded mass losses of 32.3 % and 5.42 %, respectively. Also, the outer heart- wood and inner heartwood of the E. robusta MSDFZ felled trees were highly resistant (5.42 % and 6.99 %). CSZ wood species were less naturally resistant to C. polyzona attack than those harvested from MSDFZ, which appeared to be less susceptible and more naturally resistant to decay by C. polyzona. Both species are feasible for use as transmission line poles; however, trees from both ecological zones would need chemical preservatives to improve their service life, especially for outdoor applications.